2021
DOI: 10.1002/chem.202101961
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Iod(az)olium Salts – Potent Halogen‐Bond Donors in Organocatalysis

Abstract: This article describes the application of N-heterocyclic iod(az)olium salts (NHISs) as highly reactive organocatalysts. A variety of mono-and dicationic NHISs are described and utilized as potent XB-donors in halogen-bond catalysis. They were benchmarked in seven diverse test reactions in which the activation of carbon-and metal-chloride bonds as well as carbonyl and nitro groups was achieved. N-Methylated dicationic NHISs rendered the highest reactivity in all investigated catalytic applications with reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 83 publications
(246 reference statements)
1
57
0
Order By: Relevance
“…For XB donors, it has been demonstrated that cationic iodine(I)-containing species C-in particular, iodoazoliums [30][31][32][33][34][35][36][37][38][39] -effectively catalyze an extensive series of organic transformations, whereas hypervalent iodine(III) derivatives F (i.e., diaryliodonium salts) featuring two σ-holes at the iodine atom possess a greater catalytic activity than azolium-based iodine(I) species. [40][41][42][43][44][45][46][47][48][49][50][51] It is worth mentioning that diarylbromonium salts (F; X = Br) have also been reported to exhibit high catalytic activity. [52][53][54][55] Organocatalysts based on ChB donors have gained increasing attention over the last five years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For XB donors, it has been demonstrated that cationic iodine(I)-containing species C-in particular, iodoazoliums [30][31][32][33][34][35][36][37][38][39] -effectively catalyze an extensive series of organic transformations, whereas hypervalent iodine(III) derivatives F (i.e., diaryliodonium salts) featuring two σ-holes at the iodine atom possess a greater catalytic activity than azolium-based iodine(I) species. [40][41][42][43][44][45][46][47][48][49][50][51] It is worth mentioning that diarylbromonium salts (F; X = Br) have also been reported to exhibit high catalytic activity. [52][53][54][55] Organocatalysts based on ChB donors have gained increasing attention over the last five years.…”
Section: Introductionmentioning
confidence: 99%
“…, diaryliodonium salts) featuring two σ-holes at the iodine atom possess a greater catalytic activity than azolium-based iodine( i ) species. 40–51 It is worth mentioning that diarylbromonium salts ( F ; X = Br) have also been reported to exhibit high catalytic activity. 52–55…”
Section: Introductionmentioning
confidence: 99%
“…Diaryliodonium cations (Ar 2 I + ) are multipurpose reagents in organic synthesis. They have received major attention as arylating agents but attracted interest also as topochemical reagents and noncovalent catalysts. Their ability to form attractive interaction was recognized long ago, when Alcock introduced the concept of secondary bonding . After the rationalization of these interactions as charge-assisted halogen bonds (HaBs), the use of diaryliodonium cations as tectons in crystal engineering became more and more common. , This increased interest was favored by the unique geometric features of these HaB donors with respect to other organic tectons.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that hypervalent iodine­(III) derivatives (i.e., diaryliodonium salts) featuring two σ-holes at the iodine atom exhibit remarkable Lewis acidity, , and they possess greater catalytic activity than azolium-based iodine­(I) derivatives. Current progress in the development of efficient diaryliodonium-based noncovalent organocatalysts has focused on two complementary directions: (i) functionalization of the aryl rings in the cation, ,, as well as changing the aryl to heteroaryl moieties; and (ii) preparation of chelating dinuclear iodine­(III) species (Figure ). , It is worthwhile to mention that diarylbromonium salts were also reported to exhibit high catalytic activity recently. , …”
Section: Introductionmentioning
confidence: 99%